A case report of application of posterior pharyngeal flap in resection and reconstruction of posterior pharyngeal wall carcinomas located at the level of the cricoid cartilage. Issue 7 (February 2019) - Li, Lianhe; Zou, Liangyu; Fang, Jugao
Abstract: Rationale: posterior pharyngeal wall carcinomas located at the level of the cricoid cartilage is a rare occurrence. Surgical treatment is a dilemma owing to the retention of laryngeal function Patient concerns: A 56-year-old man underwent a "resection of left cervical tumor" at another hospital. Postoperative pathological report noted a left metastatic squamous cell carcinoma of the neck. Neck-enhanced computed tomography (CT) revealed thickening of the right posterior pharyngeal wall, and an image of soft tissue density was present on the posterior pharyngeal wall with a size of approximately 1.0 × 1.5 cm. Diagnosis: Hypopharyngeal carcinoma (T1N2M0). Interventions: We performed operation on a patient who suffered from posterior pharyngeal wall carcinomas at the level of the cricoid cartilage. The postoperative defects were repaired with posterior pharyngeal flaps. Outcomes: The patient with posterior pharyngeal flap after operation survived without necrosis, the neck wounds of patient healed in 1 stage, and the phonation, swallowing and respiratory function was good. Lessons: The application of posterior pharyngeal flap to repair defects due to posterior pharyngeal wall carcinomas that were located at the level of the cricoid cartilage after resection is an effective reconstruction method that is easy to use and has excellent repair effects.